Oral health status and parental perception of dental anxiety of attention deficit hyperactivity disorder and nonattention deficit hyperactivity disorder children in Bengaluru city: A cross-sectional study - F Farhanaz; R Yashoda; Manjunath P Puranik (Wolters Kluwer Medknow Publications, 2018)
Context: Attention deficit hyperactivity disorder (ADHD) is a complex, multifactorial disorder which is characterized by the symptoms of inattention and/or impulsivity and hyperactivity. In children with ADHD, cognitive and executive functions may be impaired leading to significant behavioral problems that may affect oral health. There is an extreme paucity of the studies related to oral health and dental anxiety among children with ADHD. Aim: The aim of this study is to assess and compare oral health status and parental perception of dental anxiety among ADHD and non-ADHD children. Materials and Methods: A cross-sectional comparative study was conducted among 100 ADHD and 100 non-ADHD children aged 6-17 years in Bengaluru city. A structured validated pro forma was used to collect demographic details, Decayed, Missing, and Filled Teeth (DMFT)/dmft, and gingival index (GI). The Dental Subscale of Children's Fear Survey Schedule was used to assess parental perception of dental anxiety. Data were analyzed using Chi-square test, Mann-Whitney U-test, and Pearson's correlation test (P < 0.05). Results: DMFT was significantly higher in ADHD (1.60 ± 1.6) than in non-ADHD group (1.15 ± 1.32) (P = 0.04). There was no significant difference between the groups for GI (P = 0.3). ADHD children exhibited significantly higher dental anxiety when compared to non-ADHD children (P < 0.001). Dental anxiety was significantly related to the caries experience among ADHD group (P < 0.001). Conclusion: Children with ADHD exhibited a poorer oral health status and higher dental anxiety than non-ADHD children. Hence, there is a need for diligent preventive dental care.